2016
DOI: 10.1002/ajcp.12093
|View full text |Cite
|
Sign up to set email alerts
|

Lamp Lighters and Sidewalk Smoothers: How Individual Residents Contribute to the Maintenance of the Urban Commons

Abstract: Research on collective efficacy in urban neighborhoods has focused predominantly on whether a community can regulate local behavior and spaces and less on how they do so. This study pursues the latter question by examining the social regularities that create collective efficacy, measured as the behavioral composition of a neighborhood (i.e., the extent to which each individual contributes to a social regularity). This perspective is applied to the database of requests for non-emergency government services rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The issue of how communities within information systems might convey into communities of people and establishments [229] is a topic that is worthy of significant interest. Choe et al [230] showed that the economic fates of retailing and local communities are often intertwined.…”
Section: Community As a Platformmentioning
confidence: 99%
“…The issue of how communities within information systems might convey into communities of people and establishments [229] is a topic that is worthy of significant interest. Choe et al [230] showed that the economic fates of retailing and local communities are often intertwined.…”
Section: Community As a Platformmentioning
confidence: 99%
“…This approach promises to foster innovative solutions via joint experiences, resources and skills (Nabatchi et al, 2017;Torfing et al, 2019). Such a collaborative approach is expected to provide higher-quality services and services that meet users' needs (T. O'Brien, 2016;Torfing et al, 2021). Furthermore, co-creation processes seem to involve vulnerable groups better than traditional types of participation (Brandsen, 2021).…”
Section: Introductionmentioning
confidence: 99%